EMPOWERMENT, PARTICIPATION, AND APPARATUS CAPACITY: DYNAMICS OF VILLAGE FUND MANAGEMENT IN SUPPORTING SUSTAINABLE DEVELOPMENT GOALS (SDGs) IN BALI - I Nyoman Widhya Astawa; Ni Nyoman Kasih (Social Studies and Humanities Journal (SOSHUM), 2025)
This study analyzes the role of Village Funds as an instrument of community empowerment within the framework of the Sustainable Development Goals (SDGs) in Bali Province. Since 2015, the Village Fund has served as a national strategic policy focusing not only on infrastructure development but also on strengthening the social, economic, cultural, and environmental capacities of rural communities. Bali was selected due to its unique dual village structure—administrative (desa dinas) and customary (desa adat) villages—and its economic dependency on the tourism sector. Using a mixed-methods approach, the research combined a survey of 300 beneficiary households across 10 villages with in-depth interviews, focus group discussions (FGDs), and document analysis. Results from multiple linear regression and qualitative analysis show that the Village Fund has a positive and significant effect on community empowerment and the achievement of SDGs. Community participation enhances the impact of the Village Fund on empowerment, while the capacity of village officials increases its effective utilization. Villages such as Penglipuran and Ubud demonstrate significant empowerment outcomes compared to others that remain focused on basic infrastructure. The contribution of the Village Fund aligns with key SDGs, including poverty reduction, decent work, environmental conservation, and food security. The study concludes that the Village Fund acts as a catalyst for social, cultural, and environmental transformation, recommending enhanced capacity building for village officials and community participation toward inclusive sustainable development.